2016
DOI: 10.1186/s40711-016-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

Making transnational intimacies: intergenerational relationships in Chinese-Western families in Beijing

Abstract: In this study, we explore intergenerational relationships in Chinese-Western transnational families. Our argument draws on 28 life story interviews with Chinese middle-class professionals and their Western partners in Beijing. In the context of their living arrangements in Beijing, many of these couples had close ties with their Chinese parents or in-laws, in some cases living together under the same roof. We draw on our participants' interview narratives to ask how their culturally situated, sometimes dispara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…East Asian woman-White man couples are more common than East Asian man-White woman couples (Chen & Liu, 2021;Hyun-joo Lim, 2018;Kitano et al, 1984;Liu, 2017;Nehring & Wang, 2016;Seong-kya Ha, 2002;Zurndorfer, 2018). In line with this research, we found that 73.7% of Wasian participants had a White dad and East Asian mom, χ2(1, N = 133) = 29.84, p = .001.…”
Section: Intersectionality and Identitysupporting
confidence: 79%
“…East Asian woman-White man couples are more common than East Asian man-White woman couples (Chen & Liu, 2021;Hyun-joo Lim, 2018;Kitano et al, 1984;Liu, 2017;Nehring & Wang, 2016;Seong-kya Ha, 2002;Zurndorfer, 2018). In line with this research, we found that 73.7% of Wasian participants had a White dad and East Asian mom, χ2(1, N = 133) = 29.84, p = .001.…”
Section: Intersectionality and Identitysupporting
confidence: 79%
“…Attitudes toward intermarriage have long been considered as reflecting out-group orientation (Azzolini and Guetto 2017;Jones 2012;Weber 1978Weber [1922), and, in the case of transnational intermarriage, transnational orientation in particular. Although prior research has noted a substantial increase in the number of transnational intermarriages involving Chinese nationals in recent decades (e.g., Farrer 2008;Hu 2016a;Nehring and Wang 2016), nationally representative research on attitudes toward transnational intermarriage in China remains scarce. Against this backdrop, there is a lack of empirical assessment of major theories on the formation of transnational orientation, and a number of important questions are left unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, marriage market theorists underline the importance of opportunity structure in shaping marital orientations (Becker 1991;Kalmijn 1998). Despite a lack of national statistics on the transnational marriage market in China, existing region-specific studies indicate that the opportunity structure of transnational marriage closely mirrors the geographic patterns of international migration, global exposure, and interactions enabled by socioeconomic development and transnationalization (Farrer 2008;Hu 2016a;Nehring and Wang 2016).…”
Section: Transnational Convergencementioning
confidence: 99%
“…Additionally, couples made up of middle-class Chinese professionals married to Western partners in Beijing register a lower divorce rate than Chinese marriages. Based on 28 life-experience interviews, the study shows how parenting may be an issue that triggers inter-generational conflicts, and that Chinese spouses may mediate between their Western spouses and their parents, with an ambivalent role (Nehring & Wang, 2016).…”
Section: Intermarriagesmentioning
confidence: 99%